The decision-making process between rationality and emotions - Alvino, Letizia; Franco, Massimo (International Journal of Scientific Research and Management (IJSRM), 2017)
The decision-making process has been analyzed in several disciplines (economics, social sciences,humanities, etc.) with the aim of creating models to help decision-makers in strategy formulation. TheOrganizational theory takes into account both the decision-making process of individuals and groups of acompany. Numerous models have been built, which include a wide range of psychological, environmental,hierarchical factors, all of which only account the notion of rationality. In time, such concept has come tobe considered pragmatically unrealistic and unachievable. Emotions have recently acquired anincreasingly significant position (in the academic and economic society) as important component of thedecision making-process. From this point of view neuroscience, the new branch of medical sciences couldplay a key role in studying individual decision-making processes. This article suggests that thanks toneuroscience it is possible to overcome current limitations in economics studies, for individual’s choices,which are exclusively based on the rational component.